A Conceptual Case Study on the Synchronization of Islamic Economics and Pancasila Economics in Indonesia’s Economic Development Paradigm - Gilang Ahdi Ramadhan; Ahmad Lutfi; Syukri Iska (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
This article examines the synchronization of Islamic economics and Pancasila economics within Indonesia’s national economic development paradigm through a conceptual case study approach. Indonesia’s economic development continues to face structural paradoxes between economic growth and social justice, reflecting the limitations of value-neutral and market-oriented economic models. This study positions Indonesia’s development paradigm rooted in Article 33 of the 1945 Constitution as a conceptual case to analyze how Islamic economic principles and Pancasila economic values converge and interact as an integrated ethical framework.Using qualitative library-based research, this study analyzes primary and secondary sources on Islamic economics, Pancasila economics, development philosophy, and constitutional economics published predominantly after 2015. Data are examined through philosophical-normative and conceptual-comparative analysis to identify shared values, structural alignments, and institutional challenges in synchronizing both economic systems. The findings reveal that Islamic economics and Pancasila economics share foundational principles, including social justice, welfare orientation, moral responsibility, and balanced state intervention. However, the synchronization remains constrained by policy fragmentation, symbolic application of Pancasila economics, limited institutional integration of Islamic economic instruments, and pressures from global market structures. This study argues that the integration of Islamic economic values does not represent ideological substitution but rather strengthens the substantive foundations of Pancasila economics.This research contributes theoretically by positioning synchronization as a constitutional and philosophical necessity and offers a conceptual foundation for developing a more just, inclusive, and value-based economic development model in Indonesia